Novel insights in cryptic diversity of snow and glacier ice algae communities combining 18S rRNA gene and ITS2 amplicon sequencing - Remias, Daniel; Procházková, Lenka; Nedbalová, Linda; Benning, Liane G; Lutz, Stefanie (FEMS microbiology ecology, 2023)
Melting snow and glacier surfaces host microalgal blooms in polar and mountainous regions. The aim of this study was to determine the dominant taxa at the species level in the European Arctic and the Alps. A standardized protocol for amplicon metabarcoding using the 18S rRNA gene and ITS2 markers was developed. This is important because previous biodiversity studies have been hampered by the dominance of closely related algal taxa in snow and ice. Due to the limited resolution of partial 18S rRNA Illumina sequences, the hypervariable ITS2 region was used to further discriminate between the genotypes. Our results show that red snow was caused by the cosmopolitan Sanguina nivaloides (Chlamydomonadales, Chlorophyta) and two as of yet undescribed Sanguina species. Arctic orange snow was dominated by S. aurantia, which was not found in the Alps. On glaciers, at least three Ancylonema species (Zygnematales, Streptophyta) dominated. Golden-brown blooms consisted of Hydrurus spp. (Hydrurales, Stramenophiles) and these were mainly an Arctic phenomenon. For chrysophytes, only the 18S rRNA gene but not ITS2 sequences were amplified, showcasing how delicate the selection of eukaryotic 'universal' primers for community studies is and that primer specificity will affect diversity results dramatically. We propose our approach as a 'best practice'.
Keywords: species delimitation; Chlorophyta; Chlorophyceae; ITS2 secondary structure; ledový příkrov; glacier ice algae; geny rRNA; Ice Cover; RNA ribozomální 18S; sníh; Snow; Genes, rRNA; eDNA; snow algae; cryosphere; next generation sequencing; RNA, Ribosomal, 18S